1997
DOI: 10.1001/archinte.1997.00440320068007
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Estrogen Replacement, Pravastatin, and Combined Treatment for the Management of Hypercholesterolemia in Postmenopausal Women

Abstract: Administration of conjugated estrogens resulted in potentially antiatherogenic changes in levels of non-HDL-C, HDL-C, and calculated LDL-C. The HDL-C response to combined treatment was similar to that observed in women taking conjugated estrogens alone, while the non-HDL-C and LDL-C responses to combined treatment were similar to those produced by pravastatin therapy alone. These findings support the position of the National Cholesterol Education Program that estrogen replacement, with a progestin where indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Despite the above evidences in early and surgical menopause [5,[10][11][12][13] and the results of observational studies suggesting that postmenopausal hormone replacement therapy (HRT) could be beneficial for the heart [14], randomized placebo-controlled trials (RCT) recruiting women aged 50 to 79 years have shown no benefit but instead an increased rate of cardiac and thromboembolic events [15]. Probably, the age at menopause and the years since menopause at the beginning of HRT administration may influence its effects on cardiovascular system [16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above evidences in early and surgical menopause [5,[10][11][12][13] and the results of observational studies suggesting that postmenopausal hormone replacement therapy (HRT) could be beneficial for the heart [14], randomized placebo-controlled trials (RCT) recruiting women aged 50 to 79 years have shown no benefit but instead an increased rate of cardiac and thromboembolic events [15]. Probably, the age at menopause and the years since menopause at the beginning of HRT administration may influence its effects on cardiovascular system [16].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of statins plus HRT produced significantly greater reductions in LDL than either therapy alone. In the studies by Davidson et al [27] and Herrington et al [25], statin therapy plus HRT produced dramatic 41.4% and 47.6% reductions in LDL/HDL ratios, respectively. Of note, in a preliminary report of a secondary analysis from HERS, the combination of HRT plus statin therapy produced no greater reduction in clinical events than statin therapy alone [28].…”
Section: Cardiovascular Effects Of Statins Plus Hormone Replacement Tmentioning
confidence: 97%
“…Furthermore, because both statins and HRT lower LDL through separate mechanisms, some investigators have examined whether the combination of statins and HRT is more efficacious than either one alone. Table 2 summarizes the results of five studies that have performed head-to-head comparisons of statin therapy versus HRT and in some cases statins plus HRT, in either a crossover [23][24][25] or parallel clinical trial design [26,27]. In these studies, statins were more effective than HRT at lowering LDL, whereas HRT was more effective at raising HDL.…”
Section: Cardiovascular Effects Of Statins Plus Hormone Replacement Tmentioning
confidence: 99%
“…HRT produced a smaller decrease in total cholesterol; and in LDL-cholesterol, a smaller decrease in LDLcholesterol, a smaller elevation in HDL-cholesterol and an increase in triglyceride levels [24 -28]. Combination therapy appeared to be more effective than either agent alone [28,29]. In our view, an abrupt stop of HRT may result in a decrease in these favorable effects on the plasma lipids, and this may interfere with coronary plaque stability during the acute phase of MI.…”
Section: Hrt and Cardiovascular Risk Factorsmentioning
confidence: 99%